Evaluation of antibiotic prophylaxis in C-Section patients at RSIA Hikmah Sawi - Sarah Zielda Najib; Jumiati; Teguh Setiawan Wibowo (Journal of International Multidisciplinary Research, 2024)
The Caesarean section (C-section) rate increased steadily in the past two decades in Indonesia. People have a common belief that cesarean delivery is less painful, and safer than vaginal delivery. Risk factors for maternal infection are clearly recognised, therefore Antibiotic prophylaxis at caesarean section is widely recommended to prevent maternal infection. The study was designed to evaluate antibiotic prophylaxis use for prevention of surgical site infections (SSIs). Retrospective review of medical records of all post SC patients who received antibiotic were evaluated during October 2021 to march 2022. Among 4 different antibiotics used in post SC patients, the most frequently requested were first generation cephalosporins (50,13%), third generation cephalosporins-ceftriaxone & cefotaxime (16,89% and 3,95%) and the least frequently requested were metronidazole infusion (3,86%). Antibiotic use in post SC patients are effective strategies in reducing SSIs patients which was proven by no patients with SSIs were found during the research period.